Change Blindness in Adolescents With Attention-Deficit/Hyperactivity Disorder: Use of Eye-Tracking - Hochhauser, Michal; Aran, Adi; Grynszpan, Ouriel (Frontiers in Psychiatry, 2022)
Objective. This study investigated change detection of central or marginal interest in images using a change-blindness paradigm with eye tracking. Method. 84 drug-naïve adolescents (44 with attention-deficit/hyperactivity disorder [ADHD]/40 controls with typical development) searched for a change in 36 pairs of original and modified images, with an item of central or marginal interest present or absent, presented in rapid alternation. Collected data were detection rate, response time, and gaze fixation duration, latency, and dispersion data. Results. Both groups’ change-detection times were similar, with no speed–accuracy trade-off. No between-group differences were found in time to first fixation, fixation duration, or scan paths. Both groups performed better for items of central level of interest. The ADHD group demonstrated greater fixation dispersion in scan paths for central- and marginal-interest items. Conclusion. Results suggest the greater gaze dispersion may lead to greater fatigue in tasks that require longer attention duration.